Human enhancement drugs - Ven, Katinka van de; Mulrooney, Kyle J. D.; McVeigh, Jim (Routledge studies in crime and society, 2020)
"This book serves as a reference for academics, practitioners, law enforcement and others working in the area of human enhancement drugs. Bringing together a broad spectrum of scholarly insights and research expertise, this collection examines key international issues, providing readers with a valuable knowledge base and encouraging critical discussion"--